2023
DOI: 10.1007/s40618-023-02091-7
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids and cognitive function: a walkthrough in endogenous and exogenous alterations

Abstract: Purpose The hypothalamic–pituitary–adrenal (HPA) axis exerts many actions on the central nervous system (CNS) aside from stress regulation. Glucocorticoids (GCs) play an important role in affecting several cognitive functions through the effects on both glucocorticoid (GR) and mineralocorticoid receptors (MR). In this review, we aim to unravel the spectrum of cognitive dysfunction secondary to derangement of circulating levels of endogenous and exogenous glucocorticoids. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 286 publications
0
5
0
Order By: Relevance
“…In another, long-term study evaluating the effects of TAC therapy on cognition, brain structure, and metabolism 10 years after KT, researchers concluded that TAC may lead to cognitive decline, but not alone, and other causes may also be involved [ 22 ]. On the other hand, GCs are also known to negatively affect cognition [ 23 ]. Long-term GCs therapy may cause CI, usually characterized by deficits in memory and mental processing speed [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another, long-term study evaluating the effects of TAC therapy on cognition, brain structure, and metabolism 10 years after KT, researchers concluded that TAC may lead to cognitive decline, but not alone, and other causes may also be involved [ 22 ]. On the other hand, GCs are also known to negatively affect cognition [ 23 ]. Long-term GCs therapy may cause CI, usually characterized by deficits in memory and mental processing speed [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, GCs are also known to negatively affect cognition [ 23 ]. Long-term GCs therapy may cause CI, usually characterized by deficits in memory and mental processing speed [ 23 ]. Moreover, other side effects may occur during GCs therapy, the most common of which are psychosis, mania/hypomania, depression, and anxiety [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there is evidence of improvement in brain atrophy following GC withdrawal ( 368-371 ). We have recently extensively reviewed elsewhere the contribution of GC on cognitive function ( 372 ).…”
Section: The Adverse Effects Of Prescribed Gcsmentioning
confidence: 99%
“…induces stress. And the physiological mechanisms of stress, with suppression of pre-frontal and hippocampus activity, impairing large-band attention, learning, and memory consolidation) (De Alcubierre et al, 2023;Blankenship et al, 2019;Souza-Talarico et al, 2011), provide additional explanation, as structural correlates, of the well-established scarcity effect. However, stress is not limited to scarcity situational contexts.…”
Section: Double Precarity and Cognitive Resources For Decision-making...mentioning
confidence: 99%